Status Disclosure in HIV Infected Children in Abakaliki, Ebonyi State, Southeast, Nigeria - Orji, Maria-Lauretta; Onyire, Nnamdi Benson; Onwe, Emeka Ogah (Journal of Nepal Paediatric Society, 2018)
Introduction: The emotional and psychosocial issues surrounding HIV infection make status disclosure herculean task. Many caregivers are unwilling to disclose because they are afraid of possible unpleasant outcome. The objective of this study were to determine the prevalence rate of HIV status disclosure and possible effect on ART adherence. Material and Methods: It was a cross sectional study that involved consecutive recruitment of 94 confirmed HIV infected children aged 5-17 years. Structured questionnaire was used to obtain information on socio-demographic, disclosure and adherence. Assessment of adherence was done in the clinic by direct questioning and pill count. Results: A total of 31 (33.0%) have received a form of information regarding their HIV status. The mean age of disclosure was 12.48± 2.46 years. Majority (95.5%) of the children that received full information about their HIV status were adolescents. Circumstantial disclosure was seen in 25 (80.6%) out of the 31 subjects. A total of 61.3% of HIV status disclosure was done in hospital setting by health workers and 81.8% of subjects that were given full information about HIV were from health workers in a hospital setting. There was however no relationship between adherence to ART and status disclosure (p= 0.832). Conclusion: Age of status disclosure was rather late in this study and majority of the disclosure were consequent to prevailing circumstances in the subjects’ life. A step-wise approach to disclosure that entailed giving age dependent information as from the age of seven years is therefore recommended